CCL7 Is a Negative Regulator of Cutaneous Inflammation Following Leishmania major Infection - Ford, Jill; Hughson, Angela; Lim, Kihong; Bardina, Susana V.; Lu, Wuyuan; Charo, Israel F.; Lim, Jean K.; Fowell, Deborah J. (Frontiers in Immunology, 2019)
The chemokine CCL7 (MCP3) is known to promote the recruitment of many innate immune cell types including monocytes and neutrophils to sites of bacterial and viral infection and eosinophils and basophils to sites of allergic inflammation. CCL7 upregulation has been associated with many inflammatory settings including infection, cardiovascular disease and the tumor microenvironment. CCL7’s pleotropic effects are due in part to its ability to bind numerous chemokine receptors, namely CCR1, CCR2, CCR3, CCR5 and CCR10. CCL7-blockade or CCL7-deficiency is often marked by decreased inflammation and poor pathogen control. In the context of L. major infection, CCL7 is specifically upregulated in the skin one-two weeks after infection but its role in L. major control is unclear. To determine CCL7’s impact on the response to L. major we infected WT and CCL7-/- C57BL/6 mice. L. major infection of CCL7-deficient mice led to an unexpected increase in inflammation in the infected skin two weeks post-infection. A broad increase in immune cell subsets was observed but was dominated by enhanced neutrophilic infiltration. Increased neutrophil recruitment was associated with an enhanced IL-17 gene profile in the infected skin. CCL7 was shown to directly antagonize neutrophil migration in vitro and CCL7 add-back in vivo specifically reduced neutrophil influx into the infected skin revealing an unexpected role for CCL7 in limiting neutrophil recruitment during L. major infection. Enhanced neutrophilic infiltration in CCL7-deficient mice changed the balance of L. major infected host cells with an increase in the ratio of infected neutrophils over monocytes/macrophages. To determine the consequence of CCL7 deficiency on L. major control we analyzed parasite load cutaneously at the site of infection and viscerally in the draining LN and spleen. The CCL7-/- mice supported robust cutaneous parasite control similar to their WT C57BL/6 counterparts. In contrast, CCL7-deficiency led to greater parasite dissemination and poor parasite control in the spleen. Our studies reveal a novel role for CCL7 in negatively regulating cutaneous inflammation, specifically neutrophils, early during L. major infection. We propose that CCL7-mediated dampening of the early immune response in the skin may limit the ability of the parasite to disseminate without compromising cutaneous control.